Microbial functional genes involved in nitrogen fixation, nitrification and denitrification in forest ecosystems - Levy-Booth, David J.; Prescott, Cindy E.; Grayston, Susan J. (Soil biology & biochemistry, 2014)
The understanding of nitrogen (N) cycling in forest ecosystems has undergone a major shift in the past decade as molecular methods are being used to link microorganisms to key processes in soil. The analysis of the abundance and community structure of functional genes involved in the biogeochemical cycling of N in forest soils offers an approach to directly link microbial groups to soil characteristics and ecosystem processes. The majority of N entering ecosystems is biologically-derived from fixation of atmospheric N2. Molecular studies of N-fixation use the nitrogenase reductase (nifH) marker gene, and can be used to link N-fixation to other N- and C-cycling processes. Inorganic N entering soil via N-fixation, fertilization and deposition can have several fates, depending on the soil environment and the microbial community. The loss of N from forests stands subject to fertilization and atmospheric deposition is of increasing interest as the outputs of nitrate (NO3−) and nitrous oxide (N2O) are implicated in ground water pollution and climate change, respectively. Ammonia-oxidizing bacteria (AOB) and archaea (AOA) oxidize ammonia (NH3) to NO3− as the first step of nitrification and are studied using the ammonium monooxygenase (amoA) marker. The abundance and community structure of ammonia-oxidizers is largely dependent on pH and availability of reactive N forms, and can change rapidly following N addition or after fire. These organisms can also release N2O during nitrifier denitrification or through linked nitrification–denitrification. In some forest soils, N2O emissions are correlated with genes in the denitrification pathway (napA, narG, nirK, nirS, nosZ) making these genes useful indicators of greenhouse gas (GHG) flux potential. A review of this topic is timely as there is currently much concern regarding the effect of N fertilization and deposition on North American and European forests due to the potential alteration of dissimilative N-cycling processes and the potential for increased N2O emissions in forest stands. •Functional gene studies improve models of soil function, e.g., greenhouse gas rates.•Nitrification genes (amoA) are influenced by pH and influence N2O emission.•N2O production/reduction gene abundance linked to N2O emissions in forests.